Cro-Magnon How the Ice Age gave birth to the first modern humans - Fagan, Brian (Bloomsbury Press, 2011)
Cro-Magnon reveals human society in its infacny, facing enermous environmental challenges from glaciers, predators and a rival horminid species - the Neanderthals. Cro-Magnon conveys the adaptability and ingenuity that have made humans an unmatched success as a species and enabled our ancestors to survice environmental cataclysm